IMPLEMENTASI METODE TWO STAY TWO STRAY TERHADAP PENGUASAAN MUFRADĀT SISWA - Muwafiquddin, Achmad; Anwar, Najih (Al Mi'yar: Jurnal Ilmiah Pembelajaran Bahasa Arab dan Kebahasaaraban, 2024)
Vocabulary is one of the fundamental elements in active and passive language use. To reach a mastery phase, one must be capable of applying vocabulary in communication, writing, reading, and understanding words as well as sentences. To support the mastery of vocabulary, an engaging learning method known as the "two stay two stray" method is required. The objective of this research is to measure the effectiveness of the two stay two stray method on the mastery of Arabic vocabulary among students. This study utilizes a quantitative approach, specifically a quasi-experimental design known as the One Group Pretest-Posttest Design. The research findings indicate that the two stay two stray method has proven effective in enhancing students' mastery of Arabic vocabulary, as evidenced by an increase in the average scores of students from 54.50 in the pretest to 71.68 in the posttest. The Paired Samples T-test results demonstrate a significance value (sig2-tailed) of 0.000, indicating that sig 2-tailed (0.000 < 0.05). Therefore, it can be concluded that there is a difference between the results of the pretest and posttest. It is known that the t-score < t-table with (df) n-1 of 27 (-19.249 < -2.051), hence rejecting Ho. Consequently, it can be inferred that the two stay two stray method is effective and influential in enhancing the mastery of Arabic vocabulary among 7th-grade students at eLKISI Mojokerto Junior High School.